The novel microtubule targeting agent BAL101553 in combination with radiotherapy in treatment-refractory tumor models. Issue 3 (September 2017) - Sharma, Ashish; Broggini-Tenzer, Angela; Vuong, Van; Messikommer, Alessandra; Nytko, Katarzyna J.; Guckenberger, Matthias; Bachmann, Felix; Lane, Heidi A.; Pruschy, Martin
Abstract: Background and purpose: Resistance to microtubule targeting agents (MTA) represents a major drawback in successful cancer therapy with MTAs. Here we investigated the combined treatment modality of the novel MTA BAL101553 in combination with radiotherapy in paclitaxel and epothilone-resistant tumor models. Material and methods: Multiple regimens of BAL101553, or its active moiety BAL27862 for in vitro experiments, were probed in combination with radiotherapy in P-glycoprotein-overexpressing, human colon adenocarcinoma cells (SW480) and in tubulin-mutated human NSCLC cells (A549EpoB40) and tumors thereof. Results: BAL27862 reduced the proliferative activity of SW480 and A549EpoB40 tumor cells with similar potency as in A549 wildtype cells. Combined treatment of BAL27862 with ionizing radiation in vitro resulted in an additive reduction of clonogenicity. Moreover, treatment of paclitaxel- and epothilone-resistant tumors with fractionated irradiation and different regimens of BAL101553 (a single i.v. bolus vs. oral daily) suppressed tumor growth and resulted in an extended additive tumor growth delay with strong reduction of tumor proliferation and mean tumor vessel density. Conclusions: BAL101553 is a promising alternative in taxane- and epothilone-refractory tumors as part of a combined treatment modality with ionizing radiation. Its potent antitumor effect is not only tumor cell-directed but also targets the tumor microenvironment.